Amateur - Wendelien van Oldenborgh - Pethick, Emily (Sternberg Press, 2016)
Amateur is the first comprehensive publication about Wendelien van Oldenborgh’s moving image works, and their accompanying installations. Developed over the past ten years of her practice, these works explore communication and interaction between individuals, often against the backdrop of a unique public location, in order to cast attention on repressed, incomplete, and unresolved histories. Through the staging of these encounters on film, van Oldenborgh enables multiple perspectives and voices to coexist, and brings to light political, social, and cultural relationships and how they are manifested through social interactions. The publication is generously illustrated and brings together a wealth of texts by artists, curators, and writers who have been key interlocutors with van Oldenborgh, and who each offer in-depth observations and reflections on a work from her oeuvre.
Keywords: Oldenborgh, Wendelien van -- 1962-; Geschichte 2004-2015